Dyakonons in hyperbolic metamaterials - Zapata-Rodriguez, Carlos Javier; Miret, Juan; Vukovic, Slobodan; Jaksic, Zoran (Photonics Letters of Poland, 2013)
We have analyzed surface-wave propagation that takes place at the boundary between an isotropic medium and a semi-infinite metal-dielectric periodic medium cut normally to the layers. In the range of frequencies where the periodic medium shows hyperbolic space dispersion, hybridization of surface waves (dyakonons) occurs. At low to moderate frequencies, dyakonons enable tighter confinement near the interface in comparison with pure SPPs. On the other hand, a distinct regime governs dispersion of dyakonons at higher frequencies. Full Text: PDF References Z. Ruan, M. Qiu, "Slow electromagnetic wave guided in subwavelength region along one-dimensional periodically structured metal surface", Appl. Phys. Lett. 90, 201906 (2007). CrossRef A. Yariv, P. Yeh,"Electromagnetic propagation in periodic stratified media. II. Birefringence, phase matching, and x-ray lasers", J. Opt. Soc. Am. 67, 438 (1977). CrossRef D.R. Smith, D. Schurig, "Electromagnetic Wave Propagation in Media with Indefinite Permittivity and Permeability Tensors", Phys. Rev. Lett. 90, 077405 (2003). CrossRef I.I. Smolyaninov, E. Hwang, E. Narimanov, "Hyperbolic metamaterial interfaces: Hawking radiation from Rindler horizons and spacetime signature transitions", Phys. Rev. B 85, 235122 (2012). CrossRef Z. Jacob, E.E. Narimanov, "Optical hyperspace for plasmons: Dyakonov states in metamaterials", Appl. Phys. Lett. 93, 221109 (2008). CrossRef M.I. D'yakonov, "New type of electromagnetic wave propagating at an interface", Sov. Phys. JETP 67, 714 (1988). DirectLink I.I. Smolyaninov, Y.J. Hung, C.C. Davis, "Magnifying Superlens in the Visible Frequency Range", Science 315, 1699 (2007). CrossRef J. Elser, V.A. Podolskiy, I. Salakhutdinov, I. Avrutsky, "Nonlocal effects in effective-medium response of nanolayered metamaterials", Appl. Phys. Lett. 90, 191109 (2007). CrossRef E. Popov, S. Enoch, "Mystery of the double limit in homogenization of finitely or perfectly conducting periodic structures", Opt. Lett. 32, 3441 (2007). CrossRef B. Wood, J.B. Pendry, D.P. Tsai, "Directed subwavelength imaging using a layered metal-dielectric system", Phys. Rev. B 74, 115116 (2006). CrossRef